NON-MONETARY PRICE AND CONSUMERS’ INTENTION TO BUY ONLINE - Sørebø, Anne (PEOPLE: International Journal of Social Sciences, 2018)
While online shopping is considered efficient and easy there is also another side of the medal, the consumers feeling of risk, uncertainty and strenuous when they shop online. Consumers shopping online exhibit an odd behavior of abandoning their shopping carts instead of proceeding to checkout. This behavior would be very unlikely to see in a physical store (Close & Kukar-Kinney, 2010). If this problem is not given proper examination and paid attention to, sales profit may decrease quite a bit. Retailers need to study the differences between online consumer behaviors versus in-store consumer behaviors. It is important for the online retail companies to learn about consumer behavior so that they can make changes accordingly to increase productivity. We suggests that the risk and effort related to online shopping can be viewed as an additional cost beyond the price, usually named as the nonmonetary price in the consumer behavior literature. We draw from this theory of nonmonetary price combined with what is known about the intention to purchase from online stores, to build and test a model of customers’ web store purchase intentions. Field data from 275 respondents was obtained and analyzed. The results indicate that purchase intention is influenced by the feeling of risk and effort in addition to the perceived value (such as competitive price and easily available products). The most interesting finding is that customers’ whom invest a lot of effort in, e.g., comparing stores and identifying deals seems to generate strong purchase intentions, a finding that is the opposite of what we expected to find.